DESIGNING INTEGRATED ENGLISH TEACHING MATERIAL CLASS THROUGH ONLINE LEARNING - Rani Falantika Lasut; Nurlaily Nurlaily (JALL (Journal of Applied Linguistics and Literacy), 2022)
The impact of Covid-19 causes changes in the education system in Indonesia. The presence of an unpredicted situation urges the school to adopt a learning management system for learning activities. The researchers’ aim of this study is to teach and helps the teachers in designing English teaching material through online learning. The participants in this study were eighth-grade students consisting of 28 students of junior high school at Muhammadiyah Plus Batam. This study used the ADDIE model to show as a fundamental principle in designing integrated materials. The data were collected by conducting observation, interviews, and questionnaires. The data gathered from the final evaluation is that the design material helps the student to engage more in learning English.